MoS2 Nanosheets with Widened Interlayer Spacing for High‐Efficiency Removal of Mercury in Aquatic Systems. (23rd May 2016) - Ai, Kelong; Ruan, Changping; Shen, Mengxia; Lu, Lehui
Abstract : Molybdenum disulphide (MoS2 ) has been an attractive target for investigations in the fields of catalysis, sensing, energy storage, electronics, and optoelectronics. However, its potential application in the important area of environmental cleanup has not yet been effectively explored. With an intrinsically sulfur‐rich characteristic and unique 2D structure, MoS2 should be capable of mercury capture and removal. However, successful attempts to apply MoS2 to mercury removal are quite rare, presumably because the vast majority of sulfur atoms are located inside the bulk of MoS2 and are therefore inaccessible for mercury ions. Here, the first experimental evidence that MoS2 nanosheets with widened interlayer spacing are capable of mercury capture, with an extremely high mercury uptake capacity closely matching the theoretically predicted value (2506 mg g −1 ) and the largest distribution coefficient value (3.53 × 10 8 mL g −1 ) is provided. Remarkably, a single treatment of industrial wastewater (polyvinyl chloride industry) with this modified MoS2 could efficiently reduce the mercury concentration (126 p.p.b.) below U.S. Environmental Protection Agency limits for drinking water standards. The findings open up the possibility of expanding the applications of transition metal dichalcogenides in environmental remediation. Abstract : The first experimental evidence that MoS2 nanosheets with widened interlayer spacing are capable of mercury capture, with an extremely high mercury uptake capacity and the largest distribution coefficient value is provided. A single treatment of mercury‐contaminated water with this material could efficiently reduce the mercury concentration (10 000 p.p.b.) below U.S. Environmental Protection Agency limits for drinking water standards (2 p.p.b).